Aspectos relacionados à mortalidade, infecção de corrente sanguínea associada a cateter e aspergilose em pacientes com COVID-19 em unidade de terapia intensiva - Sousa Neto, Adriana Lemos de (2024)
Introduction: The COVID-19 pandemic has impacted the entire world due to the large number of deaths and the burden on health systems caused by the high transmissibility of the virus and the severity of the clinical condition of patients, many of whom required hospitalization in the Intensive Care Unit (ICU). An additional cause for concern was the growing number of coinfections during the pandemic period, which led to higher mortality rates. Objective: identify aspects related to mortality and catheter-associated bloodstream infection (CABSI) and to report cases of COVID-19-associated aspergillosis (CAPA) in adult COVID-19 patients hospitalized in the ICU. Material and methods: This is a retrospective cohort study whose inclusion criteria were patients diagnosed with COVID-19, aged ≥ 18 years, admitted to the ICU of a Brazilian university hospital as a result of the worsening of COVID-19, admitted between March 2020 and December 2021. Results: 588 adult patients admitted to the ICU were included, of whom 55.27% died (95% CI = 51.25 - 59.29; 325/588). Invasive mechanical ventilation was the strongest predictor of risk of death in the ICU, along with advanced age and Simplified Acute Physiology Score 3 (SAPS3). Of the total number of patients evaluated, 413 had used a central venous catheter for at least 48 hours, of which 104 had positive blood cultures for fungi and/or bacteria. Most of the microorganisms found were gram-negative bacteria (55.05% of the germs), and 55.96% were resistant to three or more antibiotics. The most prevalent pathogens were Klebsiella pneumoniae (17.43%), Acinetobacter baumanni (15.6%) and Staphylococcus aureus (13.76%). In the adjusted models, only two variables were able to predict infection: obesity, which increased the chances of CABSI by 1.39 times (OR = 2.39, 95%CI: 1.36-4.22) and the number of days of central venous catheter use before infection reduced the chances by 0.05 times a day (OR = 0.91, 95%CI: 0.91-0.99). CABSI increased the patient's length of stay in the ICU and the length of hospital stay when compared to those who did not have the infection. CABSI alone was unable to affect patient mortality. Eight cases of CAPA were identified, 6 of which were possible cases and 2 probable cases. All the cases died and received corticosteroids during hospitalization. Conclusion: The majority of COVID-19 patients in the sample evaluated did not survive. Patients with a shorter duration of catheter use and obesity had a higher incidence of CABSI. As more data on coinfections and mortality in COVID-19 patients become available, there are greater opportunities for research and implementation of strategies aimed at reducing severity, mortality and impacts on health systems, considering the possibility of new waves and/or variants of the disease.